Potensi Sekretom Mesenchymal Stem Cell untuk Terapi Regeratif Penyakit Paru Fibrosis - Kartika, Ronald; Timotius, Kris Herawan (Cermin Dunia Kedokteran, 2024)
Mesenchymal stem cells (MSC) associated with anti-inflammatory, immunomodulatory, regenerative, pro-angiogenic, and anti-fibrotic properties offers a novel therapeutic approach for fibrosis lung disease. Such therapeutic effects may be attributed to the MSC-secretome, made from free soluble proteins and extracellular vesicles (EVs). This review summarizes some literature findings related to the efficacy and safety of MSC-derived products in pre-clinical models of lung diseases, demonstrating the biologically active substances contained in the MSC-secretome and its mechanisms involved in tissue regeneration. A perspective view is given on the secretome as a high-quality, safe, and effectivemedicinal product.